Separable Reversible Data Hiding using XOR and Permutation Encryption in Image” - Chandrikapure, Reysh; Dhore, Pranjal; Balani, Nisha (International Journal of Computer Sciences and Engineering, 2025)
To perk up the security as well as the quality of decrypted, recovered images, this paper proposes a classification permutation based separable-reversible data hiding in encrypted images. A classification permutation encryption in combination with the XOR-encryption is initially designed to advance the privacy of both pixel-value and pixel location. Then, each bit in the further data is embedded in the most significant bit (MSB) of the encrypted pixels which are indiscriminately chosen based on the data-hiding key in the smooth set. The quality of decrypted and recovered image can be significantly improved by exploiting the spatial correlation as the MSBs of smooth pixels are used to embed the additional data. Results of experimentation exhibit that the quality of decrypted image obtained by the proposed method is superior than to the existing methods. There is 100% probability for lossless recovery from proposed method.